2023
DOI: 10.3390/infrastructures8010012
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Capacity of Open-Ended Pipe Piles Using Machine Learning

Abstract: Pile design is an essential component of geotechnical engineering practice, and pipe piles, in particular, are increasingly being used for the support of a variety of infrastructure projects. These piles are being used with dimensions that exceed those used in the development of the most widely used design approaches. At the same time, the growth in pile dimensions calls for the evolution of the state-of-the-art at a similar pace. The objective of this study is to provide an improved prediction of pile capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It was found that the residual force significantly affected the pile shaft force and thus the pile end resistance, but not the total bearing capacity of open-ended PHC pipe piles; the penetration depth and local lateral soil resistance had significant effects on the pile shaft force and piled side shear stress [17,18]. Baturalp Ozturk et al established a prediction model of pipe pile bearing capacity using machine learning methods and verified the feasibility of this approach [19]. Michał Baca et al proposed a new method for the static test modeling of pipe piles.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the residual force significantly affected the pile shaft force and thus the pile end resistance, but not the total bearing capacity of open-ended PHC pipe piles; the penetration depth and local lateral soil resistance had significant effects on the pile shaft force and piled side shear stress [17,18]. Baturalp Ozturk et al established a prediction model of pipe pile bearing capacity using machine learning methods and verified the feasibility of this approach [19]. Michał Baca et al proposed a new method for the static test modeling of pipe piles.…”
Section: Introductionmentioning
confidence: 99%